PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH KABUPATEN SIGI - Tolley, Sukma Selviany (Katalogis, 2017)
The research is aimed to find out and analyze simultaneous and partial influence of goverment internal controlling system on the performance of goverment officials that include controlling enviroment, risk assesment, controlling activities, information and communications, and monitoring of service qualities. The research verifies the relationship of variables by involving 84 respondents who were selected through census method. The rest result show that: 1). controlling enviroment, risk assessment, controlling activities, information and communication, and monitoring of service qualities simultaneosly have influence on the performance of the goverment working units in Sigi; 2) controlling enviroment has significant influence on the performance of the goverment working units in Sigi; 3) risk assessment has significant influence on the performance of the goverment working units in Sigi; 4) controlling activities have significant influence on the performance of the goverment working units in Sigi; 5) information and communication have significant influence on the performance of the goverment working units in Sigi.Â Â